MERAJUT KEMBALI KOMUNIKASI ANTAR BUDAYA DI INDONESIA - Budi Sayoga (IKOM UMY, 2015)
lndonesia is a nation-state that have heterogeneous pattern in various aspects, This condition is potentiol for friction, conflict, and communicational gap between ethnicl tribal to happen. To minimize the occurrence of interethnic conflict, a bond of communication between cultures that is equal and convergent is needed, Wth an interactive cross cultural communication, therefore confrontation between ethnicltribal con be minimized, social tensions can be prevented, ond the integrity of the Unitary Republic of lndonesia can be maintained.